Seen Safety Performance from the Perspective of Safety Plan, Safety Behavior and Safety Culture through Management Control as a Moderating Variable: A Conceptual Framework - Jarman Setiadi (Universitas Mercu Buana, 2022)
This paper is a research design that aims to examine the factors that can affect safety performance in the chemical industry sector, several previous studies have conducted research on safety performance in the construction sector and there is still little research on safety performance in the chemical industry sector. This study uses a quantitative research design and will use hypothesis testing using PLS-SEM analysis tools as well as field studies. This study will use the entire population of the chemical industry in Banten province, which is as many as 60 companies and all of them will be sampled in this study. Practical implications: managers in the chemical industry sector companies must implement broad policies to improve safety performance to maintain business continuity by reducing the risk of work accidents.Originality/value: this researcher is one of the pioneers in research on the influence of safety planning, safety behavior, and safety culture on safety performance in the chemical industry.